EFEKTIVITAS PEMERINTAHAN PROVINSI RIAU (STUDI KASUS KEKOSONGAN WAKIL GUBERNUR TAHUN 2016) - Mhd. Rafi Yahya; M. Melta Batrawan (LPPM Universitas Abdurrab, 2018)
ABSTRACT In law number 23 of 2014, government affairs is divided into three classifications. The affairs of the administration in the regions are delegated to the regions (concurrent). The delegation of authority is at the same time the basis of the implementation of regional autonomy. For the province of Riau the implementation of government affairs is commanded by the Governor as an extension of central government affairs in the region. The governor becomes the person mandated by the people through the process of democracy to be responsible for the implementation of government affairs. For the fiscal year 2016, the Minister of Home Affairs issues a regulation concerning the Guidelines for the Preparation of Regional Income and Expenditure Budget for 2016 as set forth in the amendment of the regulation number 52 of 2015. There are several matters that must be considered by the Regional Government related to the Rencana Kerja Pemerintah (RKP), namely; economic growth, inflation, the number of poor people, and the unemployment rate. In 2016 Riau Province Governor as head of the region does not have a representative who helps the government affairs. This study looks at how the effectiveness of Riau Province government in 2016 runs. The method used in this research is qualitative, with the technique of collecting literature study data. Through this methodology we can see Riau Provincial Government for the year 2016 run effectively if dikomparisakan with the implementation of the previous year. On the contrary, Riau Province Government is not effective when compiled with Government Work Plan as stipulated in Permendagri number 52 year 2015. Keywords: effectiveness, government, province, riau, budget year 2016 ABSTRAK Dalam Undang-Undang No. 23 Tahun 2014, urusan pemerintahan dibagi kedalam tiga klasifikasi. Urusan penyelenggaraan pemerintahan di daerah dilimpahkan kepada daerah (konkuren). Pelimpahan kewenangan tersebut sekaligus menjadi dasar pelaksanaan otonomi daerah. Untuk daerah Provinsi Riau pelaksaan urusan pemerintah ini dikomandoi oleh Gubernur sebagai perpanjangan tangan urusan pemerintah pusat di daerah. Gubernur menjadi orang yang diamanahkan oleh rakyat melalui proses demokrasi untuk bertanggungjawab atas terlaksananya urusan pemerintah. Untuk tahun anggaran 2016 Menteri Dalam Negeri mengeluarkan aturan tentang Pedoman Penyusunan Anggaran Pendapatan dan Belanja Daerah Tahun 2016 yang tertuang dalam permendagri No. 52 tahun 2015. Ada beberapa hal yang harus diperhatikan oleh Pemerintah Daerah terkait Rencana Kerja Pemerintah (RKP) yakni; pertumbuhan ekonomi, inflasi, jumlah penduduk miskin, dan tingkat pengangguran. Tahun 2016 Provinsi Riau Gubernur sebagai kepala daerah tidak memiliki wakil yang membantu urusan pemerintahan. Penelitian ini melihat bagaimana efektivitas pemerintahan Provinsi Riau tahun 2016 berjalan. Metode yang digunakan dalam penelitian ini adalah kualitatif, dengan teknik pengumpulan data studi pustaka. Melalui metodologi tersebut dapat kita lihat Pemerintahan Provinsi Riau untuk tahun 2016 berjalan efektif jika dikomparisakan dengan pelaksanaan tahun sebelumnya. Namun sebaliknya bahwa Pemerintahan Provinsi Riau tidak berjalan efektif apabila dikompariskan dengan Rencana Kerja Pemerintah yang tertuang kedalam Permendagri No. 52 Tahun 2015. Kata Kunci: efektivitas, pemerintahan, provinsi, riau, tahun anggaran 2016